RFID Untuk Sistem Keamanan dan Pelacakan: Tinjauan Literatur - Zakaria, Diky; Tri Seda Mulya; Maharani, Aisyah Aira Putri; Steven, Michael (EPSILON: Journal of Electrical Engineering and Information Technology, 2024)
In an era of rapid technological development, tracking and security become very important aspects in various industrial fields. This is a response to increasingly complex global challenges. Technology that can answer this challenge is RFID. Industry managers can perform accurate inventory tracking in real-time, conduct more accurate monitoring the flow of goods, and identify potential losses due to loss or damage in the supply chain with RFID. This article reviews various articles from scienceDirect database related to the use of RFID in security and tracking systems with research questions: fields that use RFID, readers used, tags used, impact, and data communication. The method used in this paper is Systematic Literature Review (SLR). The results of this review article can illustrate that according to the majority of articles, the field that most utilizes RFID for security and tracking systems is the manufacturing field that uses passive RFID tags and readers through a wireless communication system by attaching tags to objects used and placing readers at certain accesses. The use of RFID also has various positive impacts according to the majority of articles such as being able to shorten operational time, track small objects, minimize tracking errors, and minimize the costs required.